Stakeholders analysis of merging social health insurance funds in Iran: what kind of interests they may gain or lose?. (29th August 2018) - Bazyar, Mohammad; Rashidian, Arash; Sakha, Minoo Alipouri; Doshmangir, Leila; Rahimi, Nouroddin; Ranjbar, Mohammad; Sagha Abolfazl, Seyyedeh Fatemeh; Tabatabaei Lotfi, Seyed Moussa; Olyaeemanesh, Alireza
Summary: Iran passed a Law in 2010 to merge all existing health insurance funds physically together. This stakeholder analysis aimed at revealing that what benefits the stakeholders might lose or gain as a result of merging health insurance schemes in Iran, which make them to oppose or support it. This was a qualitative study conducted in 2014. Sixty semi‐structured face‐to‐face interviews were conducted. Purposive and snowball samplings with maximum heterogeneity samples were used for selecting interviewees. Government is not willing to undertake more financial commitment. Existing health insurance schemes like Social Security Organization and minor well‐resourced health insurance funds and also worker unions are unwilling to lose their financial and organizational autonomy, to share their benefits with other less privileged groups, or face likely financial challenges in running their health facilities like hospitals. Top managers and workforces are worried to lose their job, salary, or organizational positions. Ministry of Cooperation, Labour, and Social Welfare does not want to lose its control on health insurance schemes. Ministry of Health and Medical Education and Iran Health Insurance Organization are among actors that support the insurance funds merging policy. Successful implementing of consolidation requires taking into account the interests of different stakeholders. Highlights: The behavior of decision makers being affected by conflicting interests is aligned with rational choice theory, which uses economic approach to analyze political behavior. Usually, individuals act in their own best interests and this self‐interested behavior by individuals may influence the policy process. Implementing major health policy like merging of the existing health insurance funds together in Iran influencing interests of quite wide range of powerful actors needs notable policy conideration. Diffusion of political actors like government, parliament, health insurance schemes, Ministry of Health and Medical Education, and Ministry of Collaboration, Labour, and Social Welfare, each actor with its own power, authority, responsibility, and most important conflicting/competing interests among them is a major impediment for merging health insurance schemes in Iran. In a fragmented health insurance system including multiple actors with competing interests, the actors with legal authority like government, its ministries and Parliament need to take a more political will to create a single national health scheme.